On the Number of Irreducible Linearised Coverings for Subsets in Finite Fields - Nurijanyan, Hovhannes K. (Mathematical Problems of Computer Science, 2021)
We present lower and upper bounds for the number of irreducible linearised coverings of subsets in a finite field with characteristic greater than 2. In case of finite field with characteristic equal to 2, these bounds are obtained by Alexanian.